THE LEPIDOPTERA PEST SPECIES (INSECTA, LEPIDOPTERA) ON CABBAGE CROPS IN THE VILLAGE SIBIEL (SIBIU COUNTY) ROMANIA - Cristina STANCĂ-MOISE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This paper is only a part of one two years long study about the knowledge of parasitoide insects that control the populations of the Lepidoptera pest species on the cabbage crops in the inhabitants gardens from the village Sibiel (Sibiel county), Romania. They were analysed some aspects about biology, behaviour and ethology of the phytophagous lepidoptera species on the cabbage crops.The results could help in order to establish a monitoring methodology and management concerning the four Lepidoptera species identified in the cabbage crops: Pieris brassicae (Linnaeus, 1758), Pieris rapae (Linnaeus, 1758), Mamestra brassicae (Linnaeus, 1758), Autographa gamma (Linnaeus, 1758).